NARDL 접근법을 사용한 에너지 안보와 경제성장에 대한 관계 분석 - 장국진; 김진식; 정명석; 이주연 (시스템엔지니어링학술지, 2022)
This study investigated the relationship between economic growth and energy security risk levels in Korea using linear and non-linear ARDL methods. While there are many studies on the relationship between energy consumption and economic growth, few studies focus on the relationship between energy security and economic growth considering 4A dimensions of energy security such as energy availability, accessibility, acceptability, and affordability. Energy risk index from Global Energy Institue and GDP data from world bank are used for ARDL and NARDL analysis. Our result of ARDL shows that there is no long-term relationship between energy security risk levels and economic growth. On the other hand, NARDL result shows that there is an asymmetric relationship between economic growth and energy security risk levels in the long run. The results show the importance of expending further research on ensuring energy security to policymakers.
Keywords: Energy Security; Economic Growth; Korean Economy; NARDL; Non-linear ARDL